Isolation, protocol optimization and screening of genotypes against net blotch and scald of barley in controlled condition - Dhakal, Rishap (2022)
Net blotch and scald are two economically important diseases of barley, causing significant losses in yield in Nordic and Baltic states (NBS) countries and in Sweden. Identification and deployment of resistant cultivars is the most effective method for controlling both the diseases. However, response of cultivars towards the pathogen is a complex phenomenon. It depends on the genetics of plants, environmental factors, isolates of pathogen, developmental stages of plants, and the resistance source for the plant. Due to this complexity, assessment of the cultivars reaction in the field requires consideration of multiple factors and along with that, has to face climate variability every year. Therefore, in this work, we isolated both the disease-causing pathogen from Swedish fields. A new optimized protocol was developed for culturing both pathogens in laboratory conditions. Then, using one isolate each of the two pathogens, Swedish official trial cultivars and breeding lines from NBS countries were tested for seedling-stage resistance against the two diseases using the developed optimized protocol under controlled conditions. Afterwards, Best Linear Unbiased Estimates (BLUEs) were used to categorize/rank the genotypes after scoring. Also, a rank correlation analysis was used to compare the net blotch resistance of official trial cultivars under controlled conditions and in a field experiment. 25 cultivars out of 37 showed similar resistance type in both field and controlled condition. The results of this study provide data regarding the source of resistance available in tested material and will help decision makers to recommend cultivars repleted with resistance towards both the disease.